Pericardial Effusion-Associated Hyponatremia - Ahmed A. Hanfy; Nicholas T. Manasewitsch; Bryce D. Beutler; Daniel Antwi-Amoabeng; Mohamed Elnaggar; Munadel Awad; Gurpreet S. Chahal (Case Reports in Cardiology)
Pericardial effusion has been identified as a rare cause of hyponatremia. In most patients, pericardiocentesis results in rapid correction. We describe a 67-year-old male who presented with pericardial effusion-associated hyponatremia secondary to cardiac resynchronization therapy-D placement that resolved following evacuation. In addition, we review the literature on pericardial effusion-associated hyponatremia.